2015
DOI: 10.1021/acs.joc.5b02129
|View full text |Cite
|
Sign up to set email alerts
|

Relative Rate Profiles of Functionalized Iodoarene Catalysts for Iodine(III) Oxidations

Abstract: A series of rate studies were conducted to evaluate the steric and electronic properties that govern the reactivity of iodoarene amide catalysts in the α-oxytosylation of propiophenone. A meta-substituted benzamide catalyst emerged as the most reactive. This catalyst was employed in the α-oxytosylation of a series of substituted propiophenones, returning the α-tosyloxy ketone products in excellent isolated yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…[18,19] A similar reactivity enhancing effect was observed for the o-Me-substituted iodoarene catalyst 3 by Whitehead and co-workers. [20] Furthermore, this was also observed for aryl-λ 3 -iodanes such as for pseudocyclic benziodoxole tosylates 4 introduced by Zhdankin and co-workers. [21] However, originally, the "hypervalent twist" was proposed in an early work by Goddard and co-worker for λ 5 -iodanes, as being the structural rational for the enhanced reactivity of 2-iodoxybenzoic acid 5 in alcohol oxidations.…”
Section: Introductionmentioning
confidence: 71%
“…[18,19] A similar reactivity enhancing effect was observed for the o-Me-substituted iodoarene catalyst 3 by Whitehead and co-workers. [20] Furthermore, this was also observed for aryl-λ 3 -iodanes such as for pseudocyclic benziodoxole tosylates 4 introduced by Zhdankin and co-workers. [21] However, originally, the "hypervalent twist" was proposed in an early work by Goddard and co-worker for λ 5 -iodanes, as being the structural rational for the enhanced reactivity of 2-iodoxybenzoic acid 5 in alcohol oxidations.…”
Section: Introductionmentioning
confidence: 71%
“…The catalytic activity of each of the precatalysts ( 121 – 132 , 10 mol%) was investigated as applied to α‐tosyloxylation in the presence of m CPBA (3 equiv) and p ‐TsOH (3 equiv) in CH 3 CN, Scheme 24 [138] …”
Section: Structures and Reactivities Of λ3‐ And λ5‐iodanes ‐ Substitu...mentioning
confidence: 99%
“…The investigations with o ‐, m ‐, and p ‐iodo‐amide‐precatalysts ( 121 – 123 ) revealed that the electron‐withdrawing nature of the amide group controls the progress of the reaction. The catalysis with the precatalysts o ‐ and p ‐iodo derivatives, i.e., 121 and 123 , was found to be comparatively slower than with 122 , leading to α‐tosyloxy ketone 114 in 3, 82 and >99% yields, respectively (Table 5, entries 1–3) [138] . For catalysis with 121 , both steric and inductive effects were seen to be prominent in retarding the reaction rate, whereas for 122 and 123 , only inductive effect was found to be decisive.…”
Section: Structures and Reactivities Of λ3‐ And λ5‐iodanes ‐ Substitu...mentioning
confidence: 99%
See 1 more Smart Citation
“…[25,26] A similar reactivity enhancing effect was observed for the o-Me-substituted iodoarene catalyst 3 by Whitehead and co-workers. [27] Furthermore, this was also observed for aryl-λ 3 -iodanes such as for pseudocyclic benziodoxole tosylates 4 introduced by Zhdankin and co-workers. [28] However, originally, the "hypervalent twist" was proposed in an early work by Goddard and co-workers for λ 5 -iodanes, as being the structural rational for the enhanced reactivity of 2-iodoxybenzoic acid 5 in alcohol oxidations.…”
Section: Introductionmentioning
confidence: 99%